CSH Program or the American way of life. Californian domestic icons of the 50s - Carlos L. Marcos (VLC Arquitectura)
After World War II a new order emerged amongst the ruins, the devastation and the Allied triumph. The United States, more than any other country, emerged as a new world power with an optimism founded on victory as much as on its untouched territory and on its economy boosted by the military industrial complex. Architecture in the 50s could not avoid being part of the American dream. Would it be possible to find an architectural image to embody such an aspiration? In other words, would it be possible to conceive an architectural iconography tuned with technology, progress, freedom, individualism, and the familiar image for domestic architecture capable of assuming the symbolism and the characteristic optimism of the American way of life? That was the goal pursued by John Entenza, editor of the influential Arts & Architecture journal, and advocate of the Case Study House Program. The glazed box could assume much of the imagery associated with a new way of life for various reasons. Indeed, it served as an iconography for the domestic architecture of the period inspired in industrialisation or in the hybridisation of steel and the balloon-frame constructive system as a pretext diversely reinterpreted in the Case Study Houses later to become icons of a Californian modern domesticity.